Pengaruh Model Pembelajaran Discovery Learning Berbantuan Software Geogebra Terhadap Motivasi Belajar Siswa Kelas VIII SMP Negeri 6 Medan - Cahaya Tambunan; Nurhasanah Siregar (Departement of Mathematics Education, 2024)
This research aims to determine the influence of Discovery Learning assisted by Geogebra Software on the learning motivation of eighth-grade students at SMP Negeri 6 Medan. This is a quantitative study with the posttest-only control group design for student motivation data and a pretest-posttest control group design for supporting data in the form of learning outcomes. The research subjects are Class VIII A with 31 students as the experimental group and Class VIII B with 31 students as the control group. Data collection techniques in this study were conducted using questionnaires and tests. Learning motivation and mathematics learning outcomes data were analyzed using descriptive and inferential analysis. Through t-test on the learning motivation data, a significance value of 0.000 < 0.05 was obtained, and the t-value > t-table, which is 4.355 > 2.042. Therefore, H0 is rejected, and Ha is accepted, which means there is an influence between the independent variable and the dependent variable. The positive t-value indicates a positive and direct influence. It can be concluded that Discovery Learning assisted by Geogebra Software has a positive effect on improving students' learning motivation in Class VIII at SMP Negeri 6 Medan, with an average learning motivation score of 76, classified as high. In contrast, the average score in the control class is 67.16.